Inclusive Game-Based Learning with Design Thinking for Vocational Slow Learner Students - Lukitasari, Evelyne Henny; Musslifah, Anniez Rachmawati (Humaniora: Journal of Indonesia Culture and Society, 2026)
Slow-learning students in the Visual Communication Design (DKV) Expertise Program face challenges in attention, working memory, and visual information processing that are often suboptimal for conventional learning environments. Information technology-based Game-Based Learning (GBL) offers an interactive learning experience that reduces cognitive load through visualization, structured navigation, and immediate feedback. This research aims to evaluate the effectiveness of Articulate Storyline-based GBL in improving ease of learning and design performance among slow-learning students at SMK Negeri 9 Surakarta. The GBL model is developed using a design thinking approach and tested on two slow-learning students. Effectiveness is measured using the Single Ease Question (SEQ), logo design quality analysis, and task completion time. Statistical analysis employs a paired t-test and effect size calculation (Cohen’s d) to assess pedagogical impact. The SEQ results show a significant increase in perceived ease of use following GBL implementation. Student 1’s score increases from 2.4 to 6.1, while Student 2’s score increases from 2.3 to 6.2. These improvements indicate that GBL effectively supports slow-learning students in understanding learning tasks in a more structured and accessible manner. GBL features such as step-by-step interactions, mini-games, and immediate feedback help reduce cognitive barriers, improve focus, and strengthen students’ confidence in completing visual design assignments. Overall, Articulate Storyline-based GBL demonstrates effectiveness as an inclusive pedagogical approach in DKV learning and shows strong potential for wider implementation in visual-based vocational education.